Convergências e divergências entre legislações portuguesas e brasileiras no entorno dos rios urbanos - Matsugano, Erika Liria (2023)
To guarantee an ecologically balanced environment, it is necessary to conserve the areas around rivers and thus guarantee the well-being of present and future generations. Rivers that are part of the urban context can be a source of income in tourism, but they can also be a vector of tragedies and losses in the event of floods. In this context, the objective of the research seeks to analyze the convergences and divergences between the legislations, plans of the areas located around stretches of urban rivers (Brazil and Portugal) and to understand how they can be better managed with a view to preserving their environmental functions. With the specific objectives of i) differentiate the concepts of permanent preservation areas of urban rivers in Brazil and protected areas in Portugal, examining environmental legislation and existing plans in both countries; ii) understand the territorial context of the stretches of rivers analyzed by discussing a set of territorial planning plans, to contribute to the public manager’s decision-making in the face of hydrological events; iii) analyze laws and plans relating to the territory for better application in accordance with the different realities at municipal level in Portugal and Brazil in relation to the management of areas around rivers, especially for the prevention of emergency/flooding situations around rivers. The study sought to analyze the bibliography on the topic, as well as national and municipal legislation, and also conducted interviews with local managers and technicians from different sectors and entities. The urban and environmental legislation of the Brazilian and Portuguese systems was verified and how urban planning and management issues are dealt with. Since floods are a phenomenon with several disastrous consequences, the results presented the challenges and difficulties for the local manager to maintain environmental preservation and protection areas, and also how to act in cases of floods. The elaboration of mechanisms or the formulation of instruments with consistent technical criteria for tackling land use and occupation conflicts, through intermunicipal and metropolitan organs, respecting the limits of river basins. Analysis of risks and normative instruments to understand and intervene in the territory manager’s decision-making in cases of emergencies. Developing the identification and description of all elements from the actors involved, such as the territory and other elements of nature that can influence, such as soil, climate, temperature, pressure, is fundamental for the management of water resources and the preservation of the environment. The functions of each manager require greater dedication, and it is important to highlight that the task of preservation and conservation does not fall to a single department of a specific organ.